The Bacteroidetes Q-Rule: Pyroglutamate in Signal Peptidase I Substrates - Bochtler, Matthias; Mizgalska, Danuta; Veillard, Florian; Nowak, Magdalena L.; Houston, John; Veith, Paul; Reynolds, Eric C.; Potempa, Jan (Frontiers in Microbiology, 2018)
Bacteroidetes feature prominently in the human microbiome, as major colonizers of the gut and clinically relevant pathogens elsewhere. Here, we reveal a new Bacteroidetes specific feature in the otherwise widely conserved Sec/SPI (Sec translocase/signal peptidase I) pathway. In Bacteroidetes, but not the entire FCB group or related phyla, signal peptide cleavage exposes N-terminal glutamine residues in most SPI substrates. Reanalysis of published mass spectrometry data for five Bacteroidetes species shows that the newly exposed glutamines are cyclized to pyroglutamate (also termed 5-oxoproline) residues. Using the dental pathogen P. gingivalis as a model, we identify the PG2157 (also called PG_RS09565, Q7MT37) as the glutaminyl cyclase in this species, and map the catalytic activity to the periplasmic face of the inner membrane. Genetic manipulations that alter the glutamine residue immediately after the signal peptide in the pre-pro-forms of the gingipains affect the extracellular proteolytic activity of RgpA, but not RgpB and Kgp. Glutamine statistics, mass spectrometry data and the mutagenesis results show that the N-terminal glutamine residues or their pyroglutamate cyclization products do not act as generic sorting signals.